Carnosine Prevents Type 2 Diabetes-Induced Osteoarthritis Through the ROS/NF-κB Pathway - Yang, Yue; Wang, Yang; Kong, Yawei; Zhang, Xiaoning; Zhang, He; Gang, Yi; Bai, Lunhao (Frontiers in Pharmacology, 2018)
Background: The anti-inflammatory and antioxidant capacity of carnosine (CAR) has been investigated in autoimmune diseases. The aim of this study was to evaluate the potential protective effects of oral CAR supplements to ameliorate type 2 diabetes mellitus (T2DM)-induced osteoarthritis (OA) in rats and its mechanism. Methods: Seventy male Sprague–Dawley rats were randomly divided into the control group (CG, n = 10) and the T2DM group (n = 60). A rat model of T2DM was established using a high fat diet and streptozotocin (30 mg/kg, i.p.). The 41 rats that developed T2DM were chosen and randomly divided into four groups: T2DM-induced OA group (OAG, n = 11), and the T2DM-induced OA with low, moderate, and high-doses of CAR for 8 weeks group (CAR-L, CAR-M, and CAR-H, n = 10). After 13 weeks, all rats were evaluated by enzyme-linked immunosorbent assay (ELISA), histology, immunohistochemistry, and western blotting. Fibroblast-like synoviocytes (FLSs) were obtained from the knee joints of all rats. The effects of CAR on the inflammatory response in interleukin (IL)-1β-stimulated FLSs under a high glucose environment were evaluated by real-time quantitative polymerase chain reaction, western blotting, flow cytometry, and immunofluorescence. Results: The results of ELISA (IL-1β and tumor necrosis factor-α), the histological evaluation (Mankin and OARSI score), western blotting [COL2A1, matrix metalloproteinase (MMP)-3, MMP-13, IL-1β and nuclear factor-kappaB (NF-κB) p65] and immunohistochemistry (COL2A1, MMP-3, and MMP-13) indicated that oral CAR attenuated the development of T2DM-induced OA and suppressed the inflammatory response. Moreover, CAR alleviated MMP-3 and MMP-13 expression levels by decreasing reactive oxygen species content and suppressing nuclear translocation of NF-κB p65 on IL-1β-induced FLSs in a high glucose environment. Conclusions: These findings indicate that oral CAR had chondroprotective effects on T2DM-induced OA through the ROS/NF-κB pathway.